Fiqih Jinayah dalam Konteks Penegakan Hukum terhadap Pelaku Judi Online - Livia Maylisadi; Syifa Fajastia; Rayhan Riend Al-Afiq; Kharil Alfi Syahri; Riyan Saputra Sinaga (JOURNAL SAINS STUDENT RESEARCH, 2025)
The advancement of information technology has significantly contributed to the emergence of modern crimes, one of which is online gambling. Under Indonesia’s positive law, online gambling is a criminal offense regulated by the Criminal Code (KUHP) and the Electronic Information and Transactions Law (ITE Law). However, in the context of Fiqh Jināyah (Islamic criminal law), gambling is classified as a jarīmah taʿzīr a reprehensible act whose punishment is determined by the authority of the Islamic government. This study aims to analyze the status of online gambling within Fiqh Jināyah and how Islamic legal approaches provide solutions to the growing issue of online gambling. The research method used is library research with a normative and Islamic legal approach. The results show that online gambling causes both individual and social harm and contradicts the principles of Islamic law. Therefore, law enforcement against online gambling perpetrators should not only focus on criminal sanctions but also include spiritual and social rehabilitation.